Linear micromechanical stepping drive for pinhole array positioning. (7th April 2015) - Endrödy, Csaba; Mehner, Hannes; Grewe, Adrian; Hoffmann, Martin
Abstract: A compact linear micromechanical stepping drive for positioning a 7 × 5.5 mm 2 optical pinhole array is presented. The system features a step size of 13.2  µ m and a full displacement range of 200  µ m. The electrostatic inch-worm stepping mechanism shows a compact design capable of positioning a payload 50% of its own weight. The stepping drive movement, step sizes and position accuracy are characterized. The actuated pinhole array is integrated in a confocal chromatic hyperspectral imaging system, where coverage of the object plane, and therefore the useful picture data, can be multiplied by 14 in contrast to a non-actuated array.